NVMEN, the academic study of religion, and the IAHR : past, present and prospects - Jensen, Tim. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2016, ISBN: 9789004303942., 2015)
Nvmen publishes papers representing the most recent scholarship in all areas of the history of religions ranging from antiquity to contemporary history. It covers a diversity of geographical regions and religions of the past as well as of the present. The approach of the journal to the study of religion is strictly non-confessional. While the emphasis lies on empirical, source-based research, typical contributions also address issues that have a wider historical or comparative significance for the advancement of the discipline. Numen also publishes papers that discuss important theoretical innovations in the study of religion and reflective studies on the history of the discipline. Brill is proud to present this special volume of articles compiled to celebrate the occasion of the 60th anniversary of NVMEN: International Review for the History of Religions in 2014. The articles in this volume have been selected under the auspices of the International Association for the History of Religions (IAHR), and reflect critically on the past, present, and future of NVMEN, the IAHR and the study of the History of Religions.